Studies in Islamic legal theory - Weiss, Bernard G. (Leiden ; Boston [Mass.] : Brill, 2002)
This volume is a collection of studies devoted entirely to topics and issues in the field of Islamic legal theory and authored by 14 scholars known for their work in this field. The studies deal with such topics as early notions of charismatic authority.
Acknowledgements; Contributors; Editor's Introduction; PART ONE: Early Developments in Muslim Legal Theory; PART TWO: The Function of Usul al-fiqh; PART THREE: Controversies Within and Between Schools; PART FOUR: Authority, Reform, Underlying Principles; Alta Discussion; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Islamic law -- Interpretation and construction -- Congresses; Islamic law -- History -- Congresses; Droit islamique -- Interprétation -- Congrès.; Droit islamique -- Histoire -- Congrès.; RELIGION -- Islam -- Law; Islamic law; Islamic law -- Interpretation and construction; Islam; Rechtstheorie; Kongress; Alta, Utah; Rechtstheorie; Islamitisch recht; Conference papers and proceedings; History